The Racketeering of International Oil Trade: A Synergy of Economic Growth in Nigeria (Global Journal of Human-Social Science, 2019)
The study examined the impact of international trade on economic growth in Nigeria. The specific objectives of the study were: to investigate the impact of oil export on the economic growth in Nigeria; to investigate the impact of oil import on the economic growth in Nigeria: to investigate the impact of non-oil export on the economic growth in Nigeria; to investigate the impact of non-oil import on the economic growth in Nigeria. Secondary data collected from the statistical bulletin of the Central Bank of Nigeria was used. The unit root test result was conducted, using Augmented Dickey-Fuller technique which showed that all the variables were stationary though at different levels. The Johansen co-integration result revealed that all the variables in the model have a long run relationship. The estimated result disclosed that there is a negative and insignificant relationship between oil import and economic growth in Nigeria; positive and insignificant relationship between oil export and economic growth in Nigeria; positive and significant relationship between non-oil import and economic growth in Nigeria, positive and significant relationship between non-oil export and economic growth in Nigeria.
Keywords: import; export; non-oil export; non-oil import; and economic growth